Bifid choroid plexus: Always a normal fetal brain structure variant?. (10th June 2013) - Centini, Giovanni; Imperatore, Alberto; Morelli, Michele; Rosignoli, Lucia; Passamonti, Ubaldo; Caprioli, Francesco; Lituania, Mario
Abstract Choroid plexus, a fetal organ developing approximately from the sixth week of gestation, plays a fundamental role in developing fetal brain organization. As relatively little is known about the relationship between anomalies of choroid plexuses structure and their role in brain function, we examined cases of bifid choroid plexus (BCP) and discussed their potential association with lateral ventriculomegaly, other abnormal ultrasound findings, and their potential role as markers of fetal chromosomal abnormalities. In the present study, we described 23 cases of fetal BCP found in 2145 routine second trimester ultrasounds. For each patient 2D and 3D ultrasound volumes were acquired. BCP was defined as a choroid plexus whose body was divided into two portions (arms) differently located and oriented on the three spatial axes in correspondence to the lateral ventricle, in one or both sides. The entity of the separation and reciprocal orientation of the two arms was examined. The presence of BCP in a low‐risk population of pregnant women undergoing routine second trimester ultrasound was showed. Lateral ventricles significantly increased in the presence of BCP. Malformations were found in four of 23 fetuses with BCP. Pregnancy outcome was favorable only in one of these four cases. We suggest that in the presence of mono or bilateral BCP without associated abnormal ultrasound findings, a closer look at fetal brain or extra‐cranial structures is recommended. If no related abnormalities are found, serial prenatal and postnatal sonographic follow‐up should be considered. In the presence of concomitant abnormal findings, genetic counseling, fetal karyotyping and magnetic resonance imaging, if possible by gestational age, are strongly advised.